ANALISIS FAKTOR FAKTOR PENINGKATAN MINAT BELI KONSUMEN DALAM BELANJA DIGITAL - Sriwahyuni, Desi; Anggoro, Muhammad Agung; Nadeak, Bintang Ramotan; Barus, Chintia N. R.; Munawarrah, Munawarrah (JURNAL LENTERA BISNIS, 2026)
Rapid advances in digital technology have driven changes in consumer purchasing behavior, particularly through e-commerce platforms. In an increasingly competitive environment, companies are required to understand the factors that influence consumer purchase intent. This study aims to analyze the influence of influencer marketing, price perception, and consumer reviews on purchase intent. The findings indicate that trust in influencers, perceived price fairness, and reviews from other consumers are key considerations in determining purchasing decisions. This study employs a quantitative approach with a population consisting of all e-commerce users, the exact number of whom is unknown. Sampling was conducted using purposive sampling. The data analysis method used is multiple linear regression analysis. The results show that influencer marketing has a positive and significant effect on purchase intention. Price perception also has a positive and significant effect on consumer purchase intention. Additionally, consumer reviews were found to have a positive and significant effect on purchase intention. Simultaneously, influencer marketing, price perception, and consumer reviews have a significant effect on purchase intention.